PENGARUH PEMBELAJARAN SAVI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 21 MAKASSAR - Ikhbariaty Kautsar Qadry; Syahriani (Jurnal Penelitian Multidisiplin Ilmu, 2023)
This is a quantitative research that aims to determine the effect of SAVI learning model on mathematics learning outcomes of seventh grade students of SMP Negeri 21 Makassar. The sample of this study was 27 people selected by cluster random sampling technique. The instruments of this study were student math learning outcomes tests in the form of pretests and posttests with quadrilateral material, learning implementation observation sheets, student activity observation sheets, and student response questionnaires. The data obtained, then, were analyzed with descriptive and inferential statistics. The results showed that the application of SAVI learning affected the mathematics learning outcomes of seventh grade students of SMP Negeri 21 Makassar with the following description. The average mathematics learning outcomes of students in the pretest was 18.07; while in the posttest was 83.77. In addition, the increase in students' mathematics learning outcomes after the application of this learning is in the high category. This is indicated by the calculation of the average value of students' normalized gain of 0.802. Also, student activity during the learning process with this learning is in the very good category with an average of 82.63% active students. Meanwhile, 84.19% of students responded positively to the application of this learning. Finally, the implementation of this learning is included in the excellent category with an average of 95.31%.